Teaching English for Specific Purposes in Russian Universities: A Case of Moscow School of Social and Economic Sciences - Lubov V. Zavarykina (Высшее образование в России)
The paper discusses the impact of English for Specific Academic Purposes teaching methodology on developing in-house materials for the course of English for Social Sciences taught at the Moscow School of Social and Economic Sciences. The paper gives examples of the materials and provides results of their evaluation. The case study demonstrates efficiency of the approach to in-house materials development based on collaboration with faculty, teachers of English for Specific Academic Purposes in other disciplines, and students. The approach involves analysis of the materials designed at different stages of the educational process. Research results are assessed through the survey conducted among the students and interviews conducted with faculty members and teachers of English for Specific Academic Purposes. The efficiency of the employed approach makes it possible to use it as a model for developing in-house materials in similar academic contexts in non-linguistic universities.